Correlation of Longitudinal Gray Matter Volume Changes and Motor Recovery in Patients After Pontine Infarction - Wang, Peipei; Jia, Xiuqin; Zhang, Miao; Cao, Yanxiang; Zhao, Zhilian; Shan, Yi; Ma, Qingfeng; Qian, Tianyi; Wang, Jingjuan; Lu, Jie; Li, Kuncheng (Frontiers in Neurology, 2018)
The mechanisms of motor functional recovery after pontine infarction remain unclear. Here, we assessed longitudinal changes in gray matter volume (GMV) and examined the relationship between GMV and clinical outcome. Fifteen patients with unilateral pontine infarction underwent MRI and neurological exams five times during a period of six months. Another fifteen healthy participants were enrolled as the normal control group and were examined with the same protocol. The MR exam included routine protocol and a 3D T1-weighted MPRAGE scan. Changes in GMV were assessed using voxel-based morphometry (VBM). Furthermore, the correlations between GMV changes in regions of interest and clinical scores were assessed. Compared with normal controls (NC), the decreased GMVs in the contralateral uvula of cerebellum and the ipsilateral tuber of cerebellum were detected at 3rd month after stroke onset. At the 6th month after stroke onset, the decreased GMVs were detected in the contralateral culmen of cerebellum, putamen, as well as in the ipsilateral tuber/tonsil of cerebellum. Compared to NC, the PI group exhibited significant increases in GMV at each follow-up time point relative to stroke onset. Specifically, the significant GMV increase was found in the ipsilateral middle frontal gyrus and ventral anterior nucleus of thalamus at 2nd week after stroke onset. At 1st month after stroke onset, the increased GMVs in the ipsilateral middle temporal gyrus were detected. The significant GMV increase in the ipsilateral mediodorsal thalamus was noted at 3rd month after stroke onset. At the end of 6th month after stroke onset, the GMV increase was found in the ipsilateral mediodorsal thalamus, superior frontal gyrus and the contralateral precuneus. Across five times during a period of 6-month, a negative correlation was observed between mean GMV in the contralateral uvula, culmen, putamen and ipsilateral tuber/tonsil and mean FM score. However, mean GMV in the ipsilateral mediodorsal thalamus was positively correlated with mean FM score. Our findings suggest that structural reorganization of the ipsilateral mediodorsal thalamus might contribute to motor functional recovery after pontine infarction.